2019
DOI: 10.1038/s41598-019-55924-y
|View full text |Cite
|
Sign up to set email alerts
|

A Flow Induced Autoimmune Response and Accelerated Senescence of Red Blood Cells in Cardiovascular Devices

Abstract: Red blood cells (RBCs) passing through heart pumps, prosthetic heart valves and other cardiovascular devices undergo early senescence attributed to non-physiologic forces. We hypothesized that mechanical trauma accelerates aging by deformation of membrane proteins to cause binding of naturally occurring IgG. RBCs isolated from blood of healthy volunteers were exposed to high shear stress in a viscometer or microfluidics channel to mimic mechanical trauma and then incubated with autologous plasma. Increased bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Several well-known methods have been established to examine the effect of shear stresses on cells. These include viscometers used to apply uniform levels of shear stress to suspensions and rectangular microfluidic channels [ 21 , 22 , 23 ]. Devices used for observing cells under extensional flow also exist with several options for the bioscientist or bioengineer wanting to study the effects of elongational flow on cells, as will be discussed below and summarized in Table 1 .…”
Section: Experimental Methods For Extensional Stresses On Cellsmentioning
confidence: 99%
“…Several well-known methods have been established to examine the effect of shear stresses on cells. These include viscometers used to apply uniform levels of shear stress to suspensions and rectangular microfluidic channels [ 21 , 22 , 23 ]. Devices used for observing cells under extensional flow also exist with several options for the bioscientist or bioengineer wanting to study the effects of elongational flow on cells, as will be discussed below and summarized in Table 1 .…”
Section: Experimental Methods For Extensional Stresses On Cellsmentioning
confidence: 99%
“…A study by Buerck et al pointed out the importance of shear stress in the induction and progression of the autoimmune response and accelerated senescence of RBC [56]. Their results showed increased binding of IgG to the RBC membrane exposed to high shear stress, indicating conformational changes in the RBC membrane protein, most probably the senescent antigen of band 3, thus exposing epitopes to naturally occurring antibodies (Fig.…”
Section: Pathogenesis Of Aihamentioning
confidence: 95%
“…These effects have a significant dependence upon metabolic alterations, which are uniquely elicited by different stressors including nutrient depletion, Ca 2+ overload, and hyperthermia [ 18 ]. The onset of eryptosis is associated with the release of microparticles (MPs), membrane-bound vesicles 0.1–1 μm in diameter, which can also be influenced by increased shear stress [ 19 , 20 , 21 ]. Although shear stress and oxidative stress are both elevated during exercise, previous studies have indicated that short maximal exercise tests do not cause RBC-MPs or markers of eryptosis to increase [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%